Determination of Nine Antiviral Drug Residues in Animal Origin Foods by High Performance Liquid Chromatography-tandem Mass Spectrometry - Yanchao GONG; Jing ZHAO; Ying CUI; Guoxu WU (Shipin gongye ke-ji, 2023)
A method for detecting nine antiviral drug residues of nevirapine, famciclovir, abidox, acyclovir, imiquimod, memantine, amantadine, oseltamivir and morpholinoguanidine in animal origin foods such as meat, egg and milk was established by high performance liquid chromatography-tandem mass spectrometry. The samples were first extracted by 1% acetic acid-acetonitrile solution, then purified by PRiME HLB column. The nine components were separated by Sielc obelisc R column and gradiently eluted using acetonitrile-10 mmol/L ammonium acetate solution (containing 0.1% formic acid) as mobile phase. The detection of antiviral drugs was performed by tandem mass spectrometry in electrospray ionization under multiple reactions monitoring (MRM) mode. The calibration curves for the nine antiviral drugs were linear over the range , and the determination coefficients R2 was 0.9991~0.9998. The detection limit of the nine antiviral drugs ranged from 0.1~0.5 μg/kg, and quantitative limit ranged from 0.3~1.5 μg/kg. The recoveries of the nine antiviral drugs were between 82.3% and 95.7% with the relative standard deviations of 3.2%~5.9% (n=5).This method was used to detect 10 samples and compared with the standard method. The method has high accuracy and sensitivity, and can meet the detection needs of antiviral drug residues in animal origin foods.